The mosquito Anopheles (Cellia) oreios sp. n., formerly species 6 of the Australasian Anopheles farauti complex, and a critical review of its biology and relation to disease. Issue 1 (23rd December 2014) - BANGS, M. J.; TAAI, K.; HOWARD, T. M.; COOK, S.; HARBACH, R. E.
Abstract Species 6 of the Australasian Anopheles farauti sibling species complex (Diptera: Culicidae) is described and formally named Anopheles oreios Bangs & Harbach, sp. n. Adult, pupal and fourth‐instar larval specimens collected in the Baliem Valley, Papua Province, Indonesia, are characterized and compared with those of Anopheles farauti, Anopheles hinesorum, Anopheles irenicus and Anopheles torresiensis (formerly informally denoted as species 1, 2, 7 and 3, respectively). The variable wings of adult females, the male genitalia, the pupa and the fourth‐instar larva of An. oreios are illustrated and DNA sequence data are included for regions coding for sections of the mitochondrial COI and COII genes. The biology of An. oreios and its relation to malaria transmission are discussed in detail and contrasted with the biology and disease relations of some members of the An. farauti and Anopheles punctulatus sibling species complexes.